"If you do not birget [manage] then you don't belong here": a qualitative focus group study on the cultural meanings of suicide among Indigenous Sámi in arctic Norway. Issue 1 (1st January 2019) - Stoor, Jon Petter Anders; Berntsen, Gro; Hjelmeland, Heidi; Silviken, Anne
ABSTRACT: Suicide is a major public health issue across the Arctic, especially among Indigenous Peoples. The aim of this study was to explore and describe cultural meanings of suicide among Sámi in Norway. Five open-ended focus group discussions (FGDs) were conducted with 22 Sámi (20) and non-Sámi (2) participants in South, Lule, Marka, coastal and North Sámi communities in Norway. FGDs were recorded, transcribed verbatim and analysed employing thematic analysis. Six themes were developed from the analysis: "Sámi are treated negatively by the majority society", "Some Sámi face negative treatment from other Sámi", "The historic losses of the Sámi have turned into a void", "Sámi are not provided with equal mental health care", "The strong Sámi networks have both positive and negative impacts" and "'Birgetkultuvvra' might be a problem". The findings indicate that the participants understand suicide among Sámi in relation to increased problem load for Sámi (difficulties in life not encountered by non-Sámi) and inadequate problem-solving mechanisms on different levels, including lack of equal mental health care for Sámi and cultural values of managing by oneself ( "ieš birget" ). The findings are important when designing suicide prevention initiatives specifically targeting Sámi.